PENGARUH KONSENTRASI PUPUK ORGANIK CAIR (POC) BIOTON TERHADAP PERTUMBUHAN TRUBUSAN JATI UNGGUL NUSANTARA (Tectona grandis sp.) DI KEBUN PERCOBAAN COGREG UNIVERSITAS NUSA BANGSA - Putra, Suriya Adi; Satjapradja, Ombo; Hatta, Mohammad (Jurnal Nusa Sylva, 2012)
Jati Unggul Nusantara (JUN) can be propagated vegetative using Coppice System, with the addition ofBioton Liquid Organic Fertilizer. This study aimed to determine the effect of concentration on the growth Coppice Systemof JUN useful Bioton Liquid Organic Fertilizer to expectations providing information enrichment Coppice System of JUN regeneration techniques. Required 25 JUN stump and Bioton as an ingredient and requires a machete/knife, phi band, milli meter scrup, measuring ruler (cm), label, beakers, volumetric pipette, water spray, rubber gloves, tally sheets, stationery and computer processing of the data as a tool. Five levels of concentration treatments given in this study is 1). concentration of 0%(0ml /l) as control, 2). concentration of 5%, 3). concentration of 10% (10 ml / l), 4). concentration of 15% and 5). concentration of 20% with five repetitions at each concentration. Sampling was purposive sampling method and analyzed using a randomized block design (RBD). Average maximum height occurs at a concentration of 5 % ( 300.67cm ) , then 20 % ( 290.90 cm ) , 15 % ( 270.90 cm ) 10 % ( 270.30 cm ) and 0 % ( 265.17 cm ) . Coppice maximum height reached by the end of the observation 375cm at concentrations of 5 %, while the minimum height is 170cm trubusan reached at concentrations of 0 %. Average maximum diameter occurs at concentrations of 5 % with the achievements of diameter 4.29 cm, followed by a concentration of 20 % with the achievements of diameter 4.26 cm, the concentration of 15 % with the achievements of 4.16cm diameter, the concentration of 10 % with the achievements of diameter 3.91 cm and average performance the average minimum diameter is 3.87 cm occurred at concentrations of 0 % or control. Reaches a maximum diameter of 5.63 cm were artifacts at concentrations of 5 %, while achieving a minimum diameter of 2.86 cm at a concentration of 10 %, and there were no coppice disease, but there are leaf-eating caterpillar pests.